2016
DOI: 10.5586/asbp.3488
|View full text |Cite
|
Sign up to set email alerts
|

Demographic responses of boreal-montane orchid Malaxis monophyllos (L.) Sw. populations to contrasting environmental conditions

Abstract: In an age of changes in species' geographical ranges, compounded by climatic and anthropogenic impacts, it become important to know which processes and factors influence plant populations and their persistence in the long term.Here we investigated dynamic and fitness components in twelve populations of Malaxis monophyllos (L.) Sw., situated in different geographical (regions) and ecological (type of habitat) units. Although M. monophyllos is a rare species, characterized by highly fragmented, boreal-montane di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…This result contrasts with the results of other studies, where fruiting was lower in anthropogenic than in natural populations. Exceptionally low levels of fruiting were observed by Jermakowicz and Brzosko [59] in anthropogenic populations of Malaxis monophyllos. On the other hand, Pellegrino and Bellusci [84] noted an almost seven times lower fruit set in anthropogenic than in natural populations of Serapias cordigera in Italy.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This result contrasts with the results of other studies, where fruiting was lower in anthropogenic than in natural populations. Exceptionally low levels of fruiting were observed by Jermakowicz and Brzosko [59] in anthropogenic populations of Malaxis monophyllos. On the other hand, Pellegrino and Bellusci [84] noted an almost seven times lower fruit set in anthropogenic than in natural populations of Serapias cordigera in Italy.…”
Section: Discussionmentioning
confidence: 84%
“…Pollinator deficiency is often noted in anthropogenic populations [58]. Under such circumstances, increasing competition for pollinators may cause intensification of selection on floral traits by increasing pollen limitation [51,[59][60][61]. Anthropogenic habitats also offer distinct soil resources, which can shape plant traits such as their size, flower production, or nectar quantity and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, demographic surveys of M. monophyllos populations revealed that their size and dynamics are greatly influenced by the process of population renewal, and therefore depend indirectly on the potential for generative reproduction [34], which was emphasised by the low to moderate fruit set (from 1.5% to about 40%) observed in M. monophyllos populations [31,34,35]. In the context of pollination and mating mode, such outcomes can be explained by a non-rewarding, self-incompatible, pollinator-dependent system [3,36,37]. Although, there are no detailed studies regarding M. monophyllos pollination biology, and the cursory information is based only on scarce pollinator observations and estimating fruiting levels [31,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of pollination and mating mode, such outcomes can be explained by a non-rewarding, self-incompatible, pollinator-dependent system [3,36,37]. Although, there are no detailed studies regarding M. monophyllos pollination biology, and the cursory information is based only on scarce pollinator observations and estimating fruiting levels [31,35,36]. Up to now, the widest observations of visiting insects and pollinators were documented by Claessens and Kleynen [31] in the alpine M. monophyllos populations, which confirmed the earlier notes of Vöth [38] concerning fungus gnats from the Mycetophilidae family (Diptera) as the main group of successful pollinators.…”
Section: Introductionmentioning
confidence: 99%
“…Changing natural habitats have caused the extinction of many orchid species [17]. However, some orchids, especially in temperate regions of Europe and North America, have been found in anthropogenically disturbed territories, such as industrial dumps formed after the excavation and extraction of coal, iron, and some trace elements, and the fly ash dumps of thermal power plants [13,14,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%